2019
DOI: 10.3390/polym11050758
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Interfacial Adhesion of Polylactide/Poly(ε-caprolactone)/Walnut Shell Flour Composites by Reactive Extrusion with Maleinized Linseed Oil

Abstract: Novel green composites were prepared by melt compounding a binary blend of polylactide (PLA) and poly(ε-caprolactone) (PCL) at 4/1 (wt/wt) with particles of walnut shell flour (WSF) in the 10–40 wt % range, which were obtained as a waste from the agro-food industry. Maleinized linseed oil (MLO) was added at 5 parts per hundred resin (phr) of composite to counteract the intrinsically low compatibility between the biopolymer blend matrix and the lignocellulosic fillers. Although the incorporation of WSF tended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 74 publications
4
26
0
Order By: Relevance
“…These morphological characteristics probably result from the crushing process due to the hardness of this type of lignocellulosic particles. A similar morphology has been recently described for other lignocellulosic particles derived from similar crop wastes [12,37]. The size distribution presented in the particle histogram, plotted in Figure 2c, revealed that the particle sizes varied in the range of 1-35 µm whereas the mean size was ~15 µm.…”
Section: Visual Aspect Of Pla/fsf Composite Piecessupporting
confidence: 83%
See 3 more Smart Citations
“…These morphological characteristics probably result from the crushing process due to the hardness of this type of lignocellulosic particles. A similar morphology has been recently described for other lignocellulosic particles derived from similar crop wastes [12,37]. The size distribution presented in the particle histogram, plotted in Figure 2c, revealed that the particle sizes varied in the range of 1-35 µm whereas the mean size was ~15 µm.…”
Section: Visual Aspect Of Pla/fsf Composite Piecessupporting
confidence: 83%
“…This new phase can result from the combination of the added MLO with the ejected linseed oil, which potentially favored the interfacial adhesion of the composite and, thus, supports the increase in ductility and impact strength. Previous research studies about green composites based on PLA and lignocellulosic fillers processed with MLO have shown similar morphologies, which correlates well with their enhanced ductility performance [11,12,33]. Figure 5 gathers the DSC thermograms obtained during the second heating scan of the PLA and the PLS/FSF composites.…”
Section: Piecesupporting
confidence: 62%
See 2 more Smart Citations
“…The micrographs revealed that the particles were irregular in shape and presented a rough surface, more likely resulting from the crushing process due to the high hardness of this type of filler. Some granular features can also be observed, which resemble the original grainy and wavy structure of almond shell [35].…”
Section: Morphological Analysismentioning
confidence: 89%